Koperasi Syariah: Metode Dakwah Untuk Meningkatkan Ekonomi Umat - Yuli Eviyanti (IAIN Padangsidimpuan, 2016)
The perfection of islam includes regulating sharia or islamic laws. One ofislamic laws is man to man dealing that called with muamalah. Theprovision of muamalah is essentially efforts of people in order to achievewelfare and prosperity, based on the rules that have been outlined by islamiclaws. Al-Quran as Allah’s revelation is the source of all laws. ShariaCooperations is acooperation whose objectives and business activitiesprinciple based on Islamic laws, namely the Quran and As-Sunnah.Therefore, Sharia Cooperation is a strategy or methods to deliver themessage of islam (Dakwah) in the form of economic activity.